Фаридиддин Атторнинг машҳур тасаввуфий асарлари ва унда комил инсон ғоясини акс этиши (SCIENCE and SOCIETY, 2022)
This article analyzes Fariduddin Attar’s famous mystical work "Ilohiynama", if you can kill your ego in this work - you will take over the world, if you are worthy of God’s path, leave the path of lust, there is no end to the joy, you are drowning in the world of wonder, your understanding of happiness and unhappiness It is empty and meaningless, throw away these fantasies and analyze such issues.